Zoonosis that is Transmitted Through Food - Tri Budhi Murdiati; Indrawati Sendow (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2006)
Zoonosis can be transmitted through a number of routes including food of animal products . Foodborne disease is a disease transmitted through food, while zoonosis is defined as a disease that can be transmitted from animal to man or vice versa . Then, if agent in foodborne disease is a zoonotic, it could be defined as foodborne zoonosis . The outbreaks of Bovine Spongioform Encephalopathy (BSE) followed by Avian influenza (AI) have caused increasing concern in the food safety of animal products, especially after men were confirmed die from Al infection . Consumers are wondering whether the disease could be transmitted through the animal products from the infected animals . The safety of animal originated food is affected by the practices along the food chain, from farm to consumer plate . Human health hazard could enter the food at any points of the food chain . At the food preparation, some of the foodborne zoonosis can be prevented by the program of five keys for safer food, i .e. keep food clean, separate raw from cooked food, cook food thoroughly, store food at safe temperatures and use water and raw materials that are safe .   Key words : Zoonosis, foodborne disease, food safety